2021
DOI: 10.1002/open.202000344
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Ligand‐Linked Pt Nanoparticles: Tunable, Three‐Dimensional, Porous Networks for Catalytic Hydrogen Sensing

Abstract: Porous networks of Pt nanoparticles interlinked by bifunctional organic ligands have shown high potential as catalysts in micro‐machined hydrogen gas sensors. By varying the ligand among p‐phenylenediamine, benzidine, 4,4‘‘‐diamino‐p‐terphenyl, 1,5‐diaminonaphthalene, and trans‐1,4‐diaminocyclohexane, new variants of such networks were synthesized. Inter‐particle distances within the networks, determined via transmission electron microscopy tomography, varied from 0.8 to 1.4 nm in accordance with the nominal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 35 publications
(119 reference statements)
0
12
0
Order By: Relevance
“…Both micrographs strongly resemble previously published STEM of PDA-linked Pt NP networks synthesized on carbon-coated TEM grids for which STEM tomography had demonstrated that they are composed of discrete Pt NP with inter-particle distances in the range of NP diameters. 4 The STEM data thereby indicate that the procedures described in the experimental section produced a continuous layer of a microporous PDA-linked Pt NP network also on the technically relevant SiN substrate, as desired. Note that the average thickness of the catalytic layer can be estimated as 2 μm as detailed in the ESI †.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…Both micrographs strongly resemble previously published STEM of PDA-linked Pt NP networks synthesized on carbon-coated TEM grids for which STEM tomography had demonstrated that they are composed of discrete Pt NP with inter-particle distances in the range of NP diameters. 4 The STEM data thereby indicate that the procedures described in the experimental section produced a continuous layer of a microporous PDA-linked Pt NP network also on the technically relevant SiN substrate, as desired. Note that the average thickness of the catalytic layer can be estimated as 2 μm as detailed in the ESI †.…”
Section: Resultsmentioning
confidence: 74%
“…4) as well as the spectrum of PDA on a sensor membrane within the reactor module (purple), exhibit all characteristic vibrational bands of an aromatic amine: The most prominent bands can be ascribed to the d(NH) scissoring mode at 1628 cm −1 (a), the n(CC) band at 1516 cm −1 (b), and the n(CN) stretching mode at 1263 cm −1 (e). 4,13 In addition, both spectra show weak FTIR signals at 1451 cm −1 (c) and at 1308 cm −1 (d) which are ngerprints of two further n(CC) vibrations of PDA. 4,13 In comparison, the reference spectrum of Pt-PDA on Si wafer (blue curve in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another challenge in catalyst preparation is to obtain heterogeneous catalysts with high metal loading and high metal dispersion, which are key materials in some functional systems such as fuel cell catalytic electrodes, spacecraft attitude adjustment engines and sensors. Great efforts have been made in the preparation of such catalytic systems using the unprotected metal nanoclusters prepared by using the alkaline EG method that act as building blocks [ 56 , 57 , 58 , 59 , 60 , 61 ] or starting materials [ 23 , 28 , 62 , 63 , 64 , 65 , 66 , 67 ], in which a series of effective strategies for assembling the metal nanoclusters on different supports have been developed [ 18 , 23 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 ].…”
Section: Introductionmentioning
confidence: 99%